2021
DOI: 10.1109/access.2021.3106815
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Based Selection Hyper-Heuristic Model via MAP-Elites

Abstract: Combinatorial optimization problems (COPs) are paramount for real-life problems with discrete variables. Even though the number of combinations is finite, some problems exhibit exponential growth, rendering exact approaches unfeasible. So, approximate methods, such as heuristics, are customary for making fast decisions. Despite their small computational cost, each heuristic specializes in specific kinds of problems. Hence, other approaches have appeared for merging their strengths. One of these approaches is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Another article [42] proposed using an illumination algorithm called MAP-Elites to train sequence-based hyperheuristics for the balanced partition problem. It is found that training with ME yields better results even in their lousy performance levels than randomly selected heuristics.…”
Section: ) Hyper-heuristicsmentioning
confidence: 99%
“…Another article [42] proposed using an illumination algorithm called MAP-Elites to train sequence-based hyperheuristics for the balanced partition problem. It is found that training with ME yields better results even in their lousy performance levels than randomly selected heuristics.…”
Section: ) Hyper-heuristicsmentioning
confidence: 99%
“…For example, one may define a set of rules for selecting actions (heuristics) [12]. Conversely, one may just lay out a sequence of such actions and optimize said sequence [13]. Or one could resort to ideas from diverse fields, such as those from reinforcement learning [14,15], or others [16][17][18][19][20][21].…”
Section: Motivation and Significancementioning
confidence: 99%
“…Specifics aside, HHs (as a whole) have proven to be a path worth pursuing and polishing [1]. For example, Sanchez et al merged HHs with an approach designed for obtaining a variety of quality designs for a single-objective problem [13]. Such an approach is commonly referred to as an illumination algorithm since it seeks to provide insights into good designs for different ranges of the design variables.…”
Section: Motivation and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The use of quality-diversity methods such as the Map of Phenotypic Elites (MAP-Elites) [21,18] that generate multiple high-quality but diverse solutions to an optimisation problem is very well-established in the field of robotics. Increasingly the approach is finding applications in combinatorial optimisation domains such as routing [28], constrained optimisation [25] and instance-generation [2]. Specifically, the MAP-Elites algorithm generates a set of solutions to a singleobjective optimisation problem that are diverse with respect to a set of features defined by a user.…”
Section: Introductionmentioning
confidence: 99%